2011
DOI: 10.1002/anie.201006165
|View full text |Cite
|
Sign up to set email alerts
|

Divergolides A–D from a Mangrove Endophyte Reveal an Unparalleled Plasticity in ansa‐Macrolide Biosynthesis

Abstract: In‐built diversification: Four ansa macrolides, divergolides A–D (1–4), with intriguing structures were isolated from a bacterial endophyte of the mangrove tree Bruguiera gymnorrhiza. These compounds are generated by a common biogenesis from a linear precursor that undergoes various reactions to give the multicyclic structures. This remarkable plasticity results in metabolites with different antibacterial and cytotoxic properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
96
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 94 publications
(102 citation statements)
references
References 37 publications
5
96
0
1
Order By: Relevance
“…7,9,22 Another approach to ansamycin structural diversification using chain extender units has recently been reported. 23 …”
Section: Resultsmentioning
confidence: 99%
“…7,9,22 Another approach to ansamycin structural diversification using chain extender units has recently been reported. 23 …”
Section: Resultsmentioning
confidence: 99%
“…Ding et al [62] reported divergolides A-D ( 44 – 47 ) with complex and diverse structures isolated from an endophyte Streptomyces sp. HKI0576 of the mangrove tree Bruguiera gymnorrhiza in China.…”
Section: Natural Products Produced By Mangrove Actinomycetesmentioning
confidence: 99%
“…; Ding et al . ), was obtained from strain W112, an endophyte of Camptotheca acuminate . Another new ansamycin, 5, 21‐cyclic derivative of ansalactam A, was identified from XZQH‐4.…”
Section: Resultsmentioning
confidence: 99%
“…It shares many biosynthetic characteristics with divergolide D. For example, both are naphthalenic nonaketides and have the same unusual extender unit 2‐isobutyrylmalonyl‐CoA (Ding et al . ; Wilson et al . ).…”
Section: Resultsmentioning
confidence: 99%